Coding and Iterative Decoding of Concentrated Multi-level Codes for the Rayleigh Fading Channel - Al-Askary, Omar (KTH, Kommunikationssystem, CoS, 2006)
In this thesis we present the concept of concatenated multilevel codes. These codes are a combination of generalized concatenated codes with multilevel coding. The structure of these codes is simple and relies on the concatenation of two or more codes of shorter length. These codes can be designed to have large diversity which makes them attractive for use in fading channels. We also present an iterative decoding algorithm taylored to fit the properties of the proposed codes. The iterative decoding algorithm we present has a complexity comparable to the complexity of GMD decoding of the same codes. However, The gain obtained by using the iterative decoder as compared to GMD decdoing of these codes is quite high for Rayleigh fading channels at bit error rates of interest. Some bounds on the performance of these codes are given in this thesis. Some of the bounds are information theoretic bounds which can be used regardless of the code under study. Other bounds are on the error probability of concatenated multilevel codes. Finally we give examples on the implementation of these codes in adaptive coding of OFDM channels and MIMO channels. === QC 20100629